E-Module Development Based on Differentiation in Chemistry Subjects Class XI SMA Acids and Bases Solution Material - Agustina, Dwi Ita; Mustaji, Mustaji; Fatirul, Achmad Noor (EDUCATIO : Journal of Education, 2022)
Early study results on the educated participants class XII SMA Negeri 1 Kedungpring through interviews and observations shows that educated participant experience difficulty in understanding solution acids and bases material. It happens because the module used did not fill their different need in study. Survey result shows that the module desired by them is different namely text book, videos, simulations and pictures. This Study aims to develop e- modules based on differentiation in chemistry class XI SMA acids and bases solution material in order to fill the educated participant need in study.Study held at SMA Negeri 1 Kedungpring Lamongan. The Study is development study using the ADDIE model (Analysis, Design, Develop, Implement, Evaluation). Trial appropriateness product done with validation test by content expert, design expert, media experts and colleague. Furthermore validated E- module was tried out. The trial carried out in two stages namely trials _ group small (6 respondents) and trials group large (30 respondents). Data collection used are validation questionnaire and response questionnaire of educated participant. The data is in form of number then analyzed in a manner descriptive.Analysis results from material expert is 95.4 %, design expert is 92.9%, media experts is 94% and colleague is 96.9%. Based on material expert, design expert, media experts and colleague analysis, the e- module based on differentiation in chemistry class XI SMA acids and bases solution material is in very decent category to use. Trial results at little group is 94.5% meanwhile trials results at big group is 95.4%. Based on yield data trials the e-module based on differentiation in chemistry class XI SMA acids and bases solution material is in very decent category to use.